PROJECT PLANNING OF MIXED-USE BUILDING OF X MALL and APARTMENT SEMARANG - Adelia Dwi Muharroma; Sun Tong (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
The X Mall and Apartment Semarang Development Project is a mixed-use building project owned by PT. Sri Ratu with service providers, namely PT. Mitralanggeng Jaya Konstruksi. This building stands on an area of 24,173 m2 and has a building area of 101,437.45 m2. Good project planning is needed to ensure the project runs on time, quality, and cost. The aspects discussed in this study are the organizational structure, site layout, traffic management, implementation strategy and method, implementation schedule, quality planning, OHS plan, project scheduling, and budget plans. The data used to prepare this project planning includes shop drawings, technical specifications, and the Basic Unit Price Analysis of 2022 Semarang. Microsoft Excel 2021 is used to prepare cost estimates, and Microsoft Project Planning 2021 is used to prepare the implementation schedule. After preparing the project planning, the results are (1) organizational structure with a projectized organization type, (2) on the site layout, there are 3 tower cranes used to optimize work, (3) implementation strategy using the bottom-up method and using the zoning method in its implementation, (4) quality planning based on the quality plan and quality target, for OHS using HIRARC, (5) the duration of the work is 366 working days, (6) with the implementation costs needed to carry out the construction of the Mixed-Use Building of X Mall & Apartment Semarang is Rp. 207,280,106,745.16.